The indispensable whole of work and population health: How the working life exposome can advance empirical research, policy, and action - Apostolopoulos, Yorghos; Sönmez, Sevil; Thiese, Matthew S; Gallos, Lazaros K (Scandinavian Journal of Work, Environment & Health, 2024)
' ' OBJECTIVES ': 'The thesis of this paper is that health and safety challenges of working people can only be fully understood by examining them as wholes with interacting parts. This paper unravels this indispensable whole by introducing the working life exposome and elucidating how associated epistemologies and methodologies can enhance empirical research. ' ' METHODS ': 'Network and population health scientists have initiated an ongoing discourse on the state of empirical work-health-safety-well-being research. ' ' RESULTS ': 'Empirical research has not fully captured the totality and complexity of multiple and interacting work and nonwork factors defining the health of working people over their life course. We challenge the prevailing paradigm by proposing to expand it from narrow work-related exposures and associated monocausal frameworks to the holistic study of work and population health grounded in complexity and exposome sciences. Health challenges of working people are determined by, embedded in, and/or operate as complex systems comprised of multilayered and interdependent components. One can identify many potentially causal factors as sufficient and component causes where removal of one or more of these can impact disease progression. We, therefore, cannot effectively study them by an a priori determination of a set of components and/or properties to be examined separately and then recombine partial approaches, attempting to form a picture of the whole. Instead, we must examine these challenges as wholes from the start, with an emphasis on interactions among their multifactorial components and their emergent properties. Despite various challenges, working-life-exposome-grounded frameworks and associated innovations have the potential to accomplish that. ' ' CONCLUSIONS ': 'This emerging paradigm shift can move empirical work-health-safety-well-being research to cutting-edge science and enable more impactful policies and actions.